Supporting pension decisions with value clarification methods or testimonials: two studies showing mixed effects on activation and feeling of preparation - Strikwerda, Jelle; Holleman, Bregje; Hoeken, Hans (Frontiers in Behavioral Economics, 2024)
Introduction: Pension participants need appropriate support when making (complex) pension decisions. Grounded in Fuzzy-Trace Theory, we argue that suitable decisions require participants to (accurately) understand meaningful differences between decision alternatives. Based on this, we investigated the effectiveness of different types of decision support for the decision when to retire. Methods: We conducted two experiments among participants of four Dutch pension funds (Study 1: N = 2,328, Study 2: N = 500) on the effectiveness of three different types of decision support: a) a traditional pros and cons text, b) a Value Clarification Method (VCM), and c) testimonials.The studies showed mixed results. In the first study, we found an activating effect of the VCM and the testimonials: participants who received one of these two types of decision support were more likely to visit a web page with additional information. In the second study, we found no differences between the three types of decision support. Conclusion: We discuss possible explanations for the effects found, as well as implications for future (research on) pension decision support.